EVALUATION OF SKILLS FOR DOING BATIK AT BATIK COURCES - Dedeh Kurniasari; Suparno Eko Widodo; Bedjo Sujanto (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this study is to determine the level of skills for doing batik. This type of evaluation research implements a qualitative approach to the evaluation of CIPP (Context, Input, Process, Product) model. The number of samples choosen is the Institue of Doing Batiks, or Batik Skills Institut, which were taken from locations in several towns namely, Jakarta, Bogor, Depok, Bekasi and Tangerang. Data collection techniques used interview, questionnaire, observation, and collecting photographic evidence as well as research.documents. The research ‘s results cover, Aspects of formulation of the problem, the standard of learners, teacher qualifications of doing batik, the use of educational standards, curriculum of doing and financing batik skill’s program entirely meet the program criteria. Aspects of the standard formulation of the problem and the learner has met the criteria decided, while the tutor qualification of doing batik, the use of educational facilities and infrastructure standards, curriculum and program financing has not been entirely fulfilled. Aspects of the discipline and the effevtiveness of learning process has also met the criteria decided. While the evaluation of learning outcomes have not met yet fully in accordance with the evaluation criteria decided. The aspects of competency’s mastery have not also met theory, practice and mastery of competencies graduation mark the program have been met, but program participants have not assured a promising future when the participants have completed their training program so it can be asserted batik skills program continued to do some repairs. Keywords: Evaluation, skills, programs batik Implementation, the Institute of Doing Batiks, or Batik Skills Institute